Shedding light on economic opportunity: skin tone and job quality during the Great Recession. - Visser, M. Anne (Journal of Ethnic & Migration Studies, 2017)
A significant body of literature suggests that skin-tone segmentation is a salient characteristic of inter-group economic inequality in the United States. Yet, empirical investigations of this social phenomenon and its impact on labour-market outcomes for worker’s in the United States remains limited or focused on the impact of skin tone on wages. This article examines whether or not phenotypic variability in skin tone among workers influenced levels of job quality experienced during the recessionary era (2007–2012). Data from thePuerto Ricans and the Impact of the Great Recession Surveywere used to estimate a Poisson Regression with Endogenous Treatment Effects to consider the impact that variations in skin tone have on levels of job quality experienced by workers. Findings suggest evidence of skin-tone labour-market segmentation, as workers with darker skin shades experienced lower levels of job quality than those workers with lighter skin tones within and across larger racial and ethnic groups. The results also suggest important regional variations in the experience of skin-tone labour-market segmentation in the United States. The article concludes by reflecting on the implications of the findings for racial economic inequalities and patterns of social stratification in the contemporary United States.